Development of a robust UPLC-MS/MS method for the quantification of riluzole in human plasma and its application in pharmacokinetics - Zhuo Sun; Zhuo Sun; Zhuo Sun; Xin Liu; Xin Liu; Wei Zuo; Wei Zuo; Qiang Fu; Qiang Fu; Tingting Xu; Tingting Xu; Liying Cui; et al. (Frontiers Media S.A., 2023)
Introduction: The aim of the present study was to establish a simple method for the determination of riluzole in human plasma by ultraperformance liquid chromatography-tandem mass spectrometry (UPLC-MS/MS) and apply it for the determination of riluzole in amyotrophic lateral sclerosis (ALS) patients.Methods: Samples were prepared by protein precipitation and were then gradient-eluted on a column of ACQUITY UPLC® HSS T3 by using 0.1% formic acid acetonitrile and 0.1% formic acid water as the mobile phase. Detection was performed on a Xevo TQ-S tandem mass spectrometer in the multiple-reaction monitoring mode using positive electrospray ionization. Validation was performed in the range of 5-800 ng/mL.Results and discussion: Three batches of precision accuracy, selectivity, matrix effects, extraction recovery, and stability were also verified and met the requirements. The results showed that the method was reliable and successfully applied to the pharmacokinetics study of riluzole in Chinese amyotrophic lateral sclerosis patients. Meanwhile, in comparison with other prior published methods, our method has the advantages of simple sample preparation, relatively short running time, and small plasma sample consumption, which represented a high-throughput sample determination potential.